Measuring the quality of service of a university dining using SERVQUAL and development of a structural equation model - Cevallos Ampuero, Juan Manuel (2016)
Research has developed a methodology to measure the quality and develop a model of service quality using structural equations. The research was applied at the student’s cafeteria of San Marcos University. The methodology is to develop a survey technique according to SERVQUAL of 22 questions and apply them to a representative sample. Following the exploratory factor analysis (AFE) in order to determine the dimensions of service quality is made, then confirmatory factor analysis (AFC) is applied in order to quantify the relationships between variables and dimensions; and finally, is performed the structural equation model (MEE) to find out the relationship between the dimensions, which is the model of service quality. To prepare the AFE the Lisrel and SPSS software were used; and for AFC and MEE the Lisrel software was used.